Writing the survivor : the rape novel in late twentieth-century American fiction - Field, Robin E., 1976- (Clemson University Press, 2020)
"Writing the Survivor explores how rape novels place survivors at the heart of narratives of sexual violence rather than the perpetrators. This new genre of American fiction develops innovative narratological strategies to sensitively portray violent, disturbing subject matter and promote political activism in its readers"--